Virtual enterprise based on the Lotsman PLM SYSTEM as a multi-agent system - D. V. Koshutin (Вестник Дагестанского государственного технического университета: Технические науки)
Aim. Modern industrial production requires an improved level of information management. This problem can be approached by creating an information space based on a virtual enterprise model. Methods. The article presents the structure of a virtual enterprise for industrial enterprises based on the integration method chosen as a result of comparative analysis of the Lotsman product life cycle assurance system using the solution of the Askon Corporation. A virtual enterprise is considered as a multi-agent system; the description of its levels, organizational units, their relations, actions, inputs and outputs, performed tasks, environment and states is given. Each set is presented as a formula with useful explanations and comments. Results. As an example, an algorithm for producing an engineering product is presented, which demonstrates the simplicity and convenience of designing products within the developed model of production organization. Conclusion. The article proposes the developed model of a virtual enterprise based on the Lotsman PLM system in the form of a multi-agent system. The key elements and interactions of this model are described, and the convenience of the model is demonstrated on an example.